Combating Bovine Mastitis in the Dairy Sector in an Era of Antimicrobial Resistance: Ethno-veterinary Medicinal Option as a Viable Alternative Approach - Ajose, Daniel Jesuwenu; Oluwarinde, Bukola Opeyemi; Abolarinwa, Tesleem Olatunde; Fri, Justine; Montso, Kotsoana Peter; Fayemi, Omolola Esther; Aremu, Adeyemi Oladapo; Ateba, Collins Njie (Frontiers in Veterinary Science, 2022)
Bovine mastitis (BM) is the traditional infectious condition in reared cattle which may result in serious repercussions ranging from animal welfare to economic issues. Owing to the high costs associated with preventative practices and therapeutic measures, lower milk output, and early culling, bovine mastitis is accountable for most of the financial losses suffered in cattle farming. Streptococcus agalactiae, Staphylococcus aureus, Streptococcus dysgalactiae and coliform bacteria are the predominant pathogens for bovine mastitis. In addition, the occurrence of BM has been linked to lactation stage and poor management, in the latter case, the poor stabling conditions around udder hygiene. BM occurs throughout the world, with varying rates of Streptococcus agalactiae infection in different regions. Despite the modern techniques, such as the appropriate milking practices that are applied, lower levels of pathogen vulnerability may help to prevent the development of the disease, BM treatment is primarily reliant on antibiotics for both prophylactic and therapeutic purposes. Nevertheless, as a result of the proliferation of bacterial agents to withstand the antibiotic effects, these therapies have frequently proven ineffectual, resulting in persistent BM. Consequently, alternative medicines for the management of udder inflammation have been researched, notably natural compounds derived from plants. This review focuses on BM in terms of its risk factors, pathogenesis, management, the molecular identification of causative agents, as well as the application of ethno-veterinary medicine as an alternative therapy.